1996
DOI: 10.1104/pp.110.1.249
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Late Embryogenesis Abundant Protein Gene, HVA1, from Barley Confers Tolerance to Water Deficit and Salt Stress in Transgenic Rice

Abstract: A late embryogenesis abundant (LEA) protein gene, HVA7, from barley (Hordeum vulgare L.) was introduced into rice suspension cells using the Biolistic-mediated transformation method, and a large number of independent transgenic rice (Oryza sativa L.) plants were generated. Expression of the barley HVA 7 gene regulated by the rice actin 1 gene promoter led to high-level, constitutive accumulation of the HVAl protein in both leaves and roots of transgenic rice plants. Second-generation transgenic rice plants sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
451
1
9

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 926 publications
(479 citation statements)
references
References 29 publications
12
451
1
9
Order By: Relevance
“…9). A group 3 LEA from barley (HVA1) confers tolerance to water and salt stress when expressed in rice (Oryza sativa; Xu et al, 1996). Again, correlative evidence suggests that the group 3 LEAs are associated with stress, but it is shown for the first time, to our knowledge, that the pine group 3 LEAs are specifically associated with severe stress.…”
Section: Group 2 Leas Are Specifically Up-regulated During Photosynthmentioning
confidence: 96%
See 1 more Smart Citation
“…9). A group 3 LEA from barley (HVA1) confers tolerance to water and salt stress when expressed in rice (Oryza sativa; Xu et al, 1996). Again, correlative evidence suggests that the group 3 LEAs are associated with stress, but it is shown for the first time, to our knowledge, that the pine group 3 LEAs are specifically associated with severe stress.…”
Section: Group 2 Leas Are Specifically Up-regulated During Photosynthmentioning
confidence: 96%
“…The expression of genes associated with protection and repair mechanisms have been correlated with responses to stress imposition (Xu et al, 1996;Lee and Vierling, 2000;Zhang et al, 2000). We previously identified protection and repair genes as being positively regulated in response to drought and suggested that they aided in adaptation to drought stress by protecting processes within the cell (Heath et al, 2002).…”
Section: Group 2 Leas Are Specifically Up-regulated During Photosynthmentioning
confidence: 99%
“…Functional analyses of LEA proteins have been carried out under both in vitro and in vivo conditions. Studies with HVA1, a barley group 3 LEA protein, conferred tolerance to water deficit and other stress conditions (Xu et al, 1996;Sivamani et al, 2000;Maqbool et al, 2002;Rohila et al, 2002). Expression of HVA1 in japonica rice (Xu et al, 1996) and Basmati rice (Rohila et al, 2002) conferred water deficit and salt stress tolerance.…”
Section: Group 3 Leamentioning
confidence: 99%
“…With the advancement of various genomic resource, significant achievements have been made in developing salt tolerant rice cultivars through various approaches such as conventional breeding, marker assisted breeding (Xu et al 1996;Lang et al 2008;Singh et al 2011). However, identifying the naturally salt tolerant genotypes is important to enrich and broaden the genetic base which serves as a platform to search for new cultivars that can be used as novel donors of genes or QTLs for improving a particular trait.…”
Section: Introductionmentioning
confidence: 99%